BIOREMIDIASI PENCEMARAN MINYAK di SEDIMEN PANTAI BALONGAN, INDRAMAYU dengan MENGGUNAKAN BAKTERI Alcanivorax sp. TE-9 SKALA LABORATORIUM - UMROH UMROH (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2011)
Crude oil pollution in the sediments of Balongan, Indramayu are harmful to marine ecosystems. Thus it is necessary to ameliorate with bioremediation method using bacteria. The aim of this research is to know its degradation level by Alcanivorax sp. TE-9 and they may reveal the effectiveness of Alcanivorax sp. TE-9 bacteria to degrade the crude oil. Research method was in the batch culture system. Crude oil was measured using gravimetric method and oil consentration was measured using GC/MS performed for four weeks. The result of this research show that in the 28 days of analysis show oil were degraded by Alcanivorax sp. TE-9 whereas 52.923% crude oil and control 20.04%. Bacterial growth and degradation of the oil producing trend along. Bacteria that have the highest growth, will also produce high levels of degraded oil. This indicates the oil has been exploited as a source of carbon to produce energy and growth of bacteria